Subjective Outcome Evaluation of the Project P.A.T.H.S. (Secondary 2 Program): Views of the Program Participants - Daniel T. L. Shek; Catalina S. M. Ng (The Scientific World Journal)
A total of 196 secondary schools participated in the Secondary 2 Program of the Full Implementation Phase of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes). After completion of the Tier 1 Program, 30,731 students responded to the Subjective Outcome Evaluation Form (Form A) to assess their perceptions of the program, instructors, and perceived effectiveness of the program. Based on the consolidated reports submitted by the schools to the funding body, the research team aggregated the consolidated data to form a “reconstructed” overall profile on the perceptions of the program participants. Findings demonstrated that high proportions of the respondents had positive perceptions of the program and the instructors, and roughly four-fifths of the respondents regarded the program as beneficial to them. Correlation analyses showed that perceived program and instructor characteristics were positively associated with perceived benefits of the program.